Adipose-Derived Stromal Cell-Sheets Sandwiched, Book-Shaped Acellular Dermal Matrix Capable of Sustained Release of Basic Fibroblast Growth Factor Promote Diabetic Wound Healing - Shi, Xin; Jiang, Liyuan; Zhao, Xin; Chen, Bei; Shi, Wei; Cao, Yanpeng; Chen, Yaowu; Li, Xiying; He, Yusheng; Li, Chengjie; Liu, Xiaoren; Li, Xing; et al. (Frontiers in Cell and Developmental Biology, 2021)
The management of diabetic wounds is still a therapeutic challenge in clinics. ﻿Current tissue-engineering strategies for diabetic wound healing are insufficient owing to lacking an appropriate scaffold that can largely load stem cells and induce the interacted stem cells forming ﻿granulation tissue. Herein, we fabricated a book-shaped decellularized dermal matrix (BDDM). This BDDM shows a high resemblance to native dermal tissue in histology, microstructure and ingredients, is noncytotoxicity and low-immunogenicity, as well as allows adipose-derived stromal cells (ASCs) attachment and proliferation. And then, we prepared a recombinant basic ﻿fibroblast growth factor (termed as CBD-bFGF) capable of binding collagen, and then tethered on the collagen fibers of BDDM to improve the endothelial inducibility of BDDM. Finally, a functional scaffold (CBD-bFGF/BDDM) was fabricated. In-vitro and in-vivo experiments showed that the CBD-bFGF/BDDM can release the tethered bFGF with a sustained release profile, steadily inducing the interacted stem cells down ﻿endothelial differentiation. After that, ASCs were cultured to form a cells-sheet, and then sandwiched by the CBD-bFGF/BDDM, thus enlarging the number of stem cells loading in the scaffold. Using a rat model, ﻿﻿the ASC-sheets sandwiched CBD-bFGF/BDDM (ASCs/CBD-bFGF/BDDM) are capable of enhancing the formation of granulation tissue, promoting angiogenesis, and facilitating collagen deposition and remodeling. Therefore, the findings of this study demonstrate that ASCs/CBD-bFGF/BDDM could serve as a potential application for diabetic wound healing.